Hydraulic performance of BlueLay –a potential sustainable drainage material for mitigating urban road runoff - Puneeta Sreenivas; Sarah Cotterill; Fiachra O’Loughlin (Cleaner Water)
Increasing prevalence of impervious surfaces can lead to higher surface runoff and overwhelm conventional drainage systems. The limited capacity of conventional drainage systems, coupled with increased precipitation due to climate change, requires retrofitting existing infrastructure with source control Sustainable Drainage Systems (SuDS). In this study, a porous medium - BlueLay - was evaluated for its hydraulic performance as a potential sustainable drainage material. BlueLay was tested under various rainfall, gradient and material saturation conditions. BlueLay achieved a 100 % runoff reduction when subjected to a medium intensity storm of 98 mm/hr, and a 51 % runoff reduction when subjected to a high rainfall intensity of 179 mm/hr. Infiltration through BlueLay increased with material saturation, indicating higher runoff reduction capacity during longer duration storms. Saturation tests also indicated that BlueLay can absorb up to 4 × its weight in water. Saturated BlueLay also halved the peak runoff rate. Percolation tests suggested that 2 L of water percolated through dry BlueLay in 2 min. It took 8 min to infiltrate the same volume of water through a comparable volume of soil. Additionally, BlueLay begins to infiltrate water faster after successive periods of full saturation and drying. Results suggest that BlueLay in a state of partial or complete saturation could be used to attenuate road runoff by reducing both runoff volume and attenuating peak flow through infiltration and absorption. These hydraulic properties increase its capability to reduce flood risk. Further research is required to determine if BlueLay can also attenuate pollutants, in addition to quantity reduction. To determine the most suitable application for this material, the performance of BlueLay should be tested when interfaced with other porous media such as vegetated soil and gravel which are found next to roads.